(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: The aim of this study was to describe the quality of life among children patients aged 6-14 years with allergic rhinitis visiting Hai Phong Children’s Hospital for examination and treatment in 2024. Methods: A cross-sectional study was conducted on 136 patients aged 6-14 years diagnosed with allergic rhinitis at Hai Phong Chilrden’s Hospital. The PRQLQ was applied to assess quality of life among those children. Results: The mean age of the children was 10.03 ± 2.26 years. The total quality of life score according to the PRQLQ scale shows that 95.6% of pediatric patients are significantly or severely affected. A history of allergic disease is associated with the level of impact on quality of life. Conclusion: Allergic rhinitis significantly affects the quality of life among children across all five domains.